Effect of energy utilization on economic growth in Nigeria (2012)
Energy plays an important role in economic development, and being the mainstay of any economy , it plays a vital role in shaping and /or transforming the economic destiny of such a country. Different studies have attempted to test, for many countries, the causal relationship between energy and economic growth using both theoretical and empirical methods. This paper therefore analyses the relationship between energy consumption and economic growth in Nigeria. It is evident from the review that there is a causaulity running from energy consumption to economic growth. It also reveals that the positive relationship between electricty and economic growth has been justified by many authors and economists as being consistent. Based on this review, it could be concluded that the demand for energy leads to economic growth. Therefore, the energy policy regarding electricity consumption in Nigeria should be meticulously implemented in such a way that it will further boost its impact on economic growth in no small measures.